2018
DOI: 10.1177/2010105817751742
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style of nurse managers as perceived by registered nurses: A cross-sectional survey

Abstract: Given rapid changes in the health care landscape, nurse leaders need to be equipped with effective leadership skills. Those who are aware of their styles of working and its impact on their employees could adopt a better leadership style. The study aim was to assess the leadership styles of nurse leaders, as perceived by their employees. The secondary objectives were to explore differences between self-ratings and others' ratings of leadership styles, as well as correlation between perceived leadership styles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
5
6
1
Order By: Relevance
“…In Spain,[ 5 ] reports indicated that nurses showed a better TRL style over transformational, although both TL and transformational styles correlated with efficiency and job satisfaction. Our findings are also strikingly similar to the study published in Singapore[ 18 ] which indicated that TFL demonstrated positive, significant strong correlation with extra effort, effectiveness, and satisfaction. On the other hand, Asiri et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Spain,[ 5 ] reports indicated that nurses showed a better TRL style over transformational, although both TL and transformational styles correlated with efficiency and job satisfaction. Our findings are also strikingly similar to the study published in Singapore[ 18 ] which indicated that TFL demonstrated positive, significant strong correlation with extra effort, effectiveness, and satisfaction. On the other hand, Asiri et al .…”
Section: Discussionsupporting
confidence: 91%
“…This was comparable to the studies conducted in Spain,[ 5 ] Malaysia,[ 17 ] and in Singapore. [ 18 ] However, in nursing leadership, 50% of the head nurses at Iran University of Medical Sciences preferred a TRL style to transformational (29.4%) or PAL (20.6%),[ 19 ] which accords with our results. In Saudi Arabia, although nurse managers preferred transformational over TL and Laissez-faire, they did not display the ideal level of transformation leadership, The average score was only 2.55 out of 5 points,[ 20 ] which was not consistent with our results.…”
Section: Discussionsupporting
confidence: 86%
“…This is the first study, to the best of our knowledge, to examine clinical nurse managers’ transformational leadership practices in Saudi hospitals using the leadership practice inventory instruments. Our findings indicate that compared with registered nurses’ reports, clinical nurse managers consistently self‐reported their transformational leadership practices as being better, which aligns with the study of Goh et al., (2018). These findings suggest that registered nurses are less confident about their clinical nurse managers’ transformational leadership practices than managers themselves.…”
Section: Discussionsupporting
confidence: 89%
“…18 Furthermore, the nursing literature shows that those who are aware of their work styles and their impact on their employees can adopt a better leadership style. 19 However, studies comparing leadership styles adopted by managers based on their employees' attitudes are rare. The results of studies by Sellgren et al 20 and Zampieron et al 18 showed that the mean scores of nurses' preferences were higher than their real views in all domains.…”
Section: Introductionmentioning
confidence: 99%